Racial Differences in Care and Outcomes After Total Hip and Knee Arthroplasties: Did the Comprehensive Care for Joint Replacement Program Make a Difference?. (1st June 2022) - Okewunmi, Jeffrey; Mihalopoulos, Meredith; Huang, Hsin-Hui; Mazumdar, Madhu; Galatz, Leesa M.; Poeran, Jashvant; Moucha, Calin S.
Abstract : Background: There is a paucity of literature on racial differences across a full total joint arthroplasty (TJA) "episode of care" and beyond. Given various incentives, the Comprehensive Care for Joint Replacement (CJR) program in the U.S. may have impacted preexisting racial differences across this care continuum. The purposes of the present study were (1) to assess trends in racial differences in care/outcome characteristics before, during, and after TJA surgery and (2) to assess if the CJR program coincided with reductions in these racial differences. Methods: This retrospective cohort study includes data on 1, 483, 221 TJAs (based on Medicare claims data, 2013 to 2018). Racial differences between Black and White patients were assessed for (1) preoperative characteristics (Deyo-Charlson comorbidity index, patient sex, and age), (2) characteristics during hospitalization (length of stay, blood transfusions, and combined complications), and (3) postoperative characteristics (90 and 180-day readmission rates and institutional post-acute care). Additionally, Medicare payments for each period were assessed. Racial differences (Black versus White patients) were expressed in terms of odds ratios (ORs) and 95% confidence intervals (CIs) per year. A "difference-in-differences" analysis (comparing before and after CJR implementation, with non-CJR hospitals being used as controls) estimated the association of the CJR program with changes in racial differences. Results: In both 2013 and 2018, Black patients (n = 74, 390; 5.0%) were more likely than White patients to have a higher Deyo-Charlson comorbidity index (score of >0) (OR = 1.32 [95% CI = 1.28 to 1.36] and OR = 1.32 [95% CI = 1.28 to 1.37]), to require more transfusions (OR = 1.55 [95% CI = 1.49 to 1.62] and OR = 1.77 [95% CI = 1.56 to 2.01]), to be discharged to institutional post-acute care (OR = 1.40 [95% CI = 1.36 to 1.44] and OR = 1.49 [95% CI = 1.43 to 1.56]), and to be readmitted within 90 days (OR = 1.38 [95% CI = 1.32 to 1.44] and OR = 1.21 [95% CI = 1.13 to 1.29]) (p < 0.05 for all). Adjusted difference-in-differences analyses demonstrated that the CJR program coincided with reductions in racial differences in 90-day readmission (−1.24%; 95% CI, −2.46% to −0.03%) and 180-day readmission (−1.28%; 95% CI, −2.52% to −0.03%) (p = 0.044 for both). Conclusions: Racial differences persist among patients managed with TJA. The CJR program coincided with reductions in some racial differences, thus identifying bundle design as a potential novel strategy to target racial disparities. Level of Evidence: Prognostic Level III . See Instructions for Authors for a complete description of levels of evidence.